P181 tACS frequency dependent changes in corticospinal excitability revealed using TMS mapping. Issue 3 (March 2017) - van de Ruit, M.; McAllister, C.; Grey, M.
Abstract : Transcranial alternating current stimulation (tACS) has been suggested to entrain neuronal oscillations leading to changes in motor behaviour and corticospinal excitability (CSE). Reports characterising the effect of tACS on CSE are equivocal despite tACS after-effects being ascribed to changes in synaptic plasticity. All studies to date assessing tACS-induced CSE have used single pulse TMS at a single intensity. However, this method might not reveal shifts in the corticospinal representation or unequal expansion of the cortical representation. The present study aimed to investigate the effect of tACS on CSE using TMS maps, with a stimulation frequency within (20 Hz) and outside (140 Hz) the traditional beta band for the motor system. Eleven participants visited the lab on three separate occasions to receive 10 min of sham stimulation or tACS at 1 mA and either 20 or 140 Hz. Stimulating electrodes (4 × 4 cm) were placed over the motor representation of the first dorsal interosseous (FDI) muscle and contralateral orbit. A novel rapid TMS mapping method was employed to assess the FDI motor representation before and 10–35 min after tACS. The difference in TMS map area and centre of gravity (COG) before and after stimulation were analysed. On average, map area increased after 140 Hz and decreased after 20 Hz tACS. A repeated measures ANOVA revealed no significant effect for either FREQUENCY ( P = 0.07), TIME ( P = 0.86) or a FREQUENCY'TIME interaction ( P = 0.34). Based on variability in the baseline measures we identified five participants with increased map area following 140 Hz tACS, whilst following 20 Hz tACS map area decreased for three participants. On average COG was displaced 5 ± 3 mm in the post maps compared to the baseline map. However, COG were not systematically displaced in either the x (xDisp: FREQUENCY: P = 0.38, TIME: P = 0.83, FREQUENCY'TIME: P = 0.83) or y direction (yDisp: FREQUENCY: P = 0.23, TIME: P = 0.97, FREQUENCY'TIME: P = 0.94) In conclusion, no main effect of tACS was found on CSE using TMS mapping. Nonetheless, these pilot data suggest that 10 min of 20 Hz stimulation may inhibit excitability and 140 Hz stimulation may facilitate excitability, in line with our hypothesis. This effect is masked by significant variability in the response with only a third to a half of the participants showing a changes in CSE following tACS, which is in line with reports for tDCS.